Chemical Characterization, Antimicrobial and Antioxidant Properties of Mentha spicata L. Essential Oil - Nikšić, Haris; Durić, Kemal; Omeragić, Elma; Nikšić, Hedija; Muratović, Samija; Bečić, Fahir (Bulletin of Chemists and Technologists of Bosnia and Herzegovina, 2018)
The aim of the present study was to examine chemical composition, antibacterial and antioxidative activity of essential oil extracted from the leaf of Mentha spicata. The essential oil composition was investigated by GC/MS. Thirty three components were identified, accounting for 98,9% of the essential oil. Dominant components were carvone (56,4%), limonene (16,2%), 1,8 cineole  (7%), β-pinene (2,4) and α- terpinene (2,3%). Agar disk diffusion assay was used to evaluate antibacterial activity of essential oil. The essential oil exhibited significant level of antibacterial activity against all tested bacterial strains. In general, Gram-negative bacteria were more susceptible to M. spicata essential oil than Gram-positive bacteria. E coli was the most sensitive of the microorganisms to the antibacterial activity of M. spicata essential oil. The 2,2-diphenyl-l-1-phthydrazide (DPPH) radical removal method was used for evaluating the antioxidant potential of the essential oils.. The result showed a considerable level of antioxidant activities of the essential oil investigated with (IC50 = 41, 23 µg/mL).  Based on our results, M. spicata essential oil with a strong antioxidant and antibacterial activities, could serve as a safe natural antioxidant and antiseptic supplements in the pharmaceutical and food industry.